Rise with the sun determining what makes Avatar : bthe last airbender effective as an animated television series a content analysis - Regalado, Gary Ian
This study shall be a content analysis of the popular animated television series Avatar: The Last Airbender. Its purpose is to determine what made the series so effective while using the concepts of feminism, the ideological apparatus, Marxism, and the psychoanalytical approach as tools. The content to be analyzed in this paper shall be entirety of the Last Airbender series. These shall include all 3 seasons: Book 1: Water, Book 2: Earth, and Book 3: Fire. The researcher shall go through each episode individually, and through the use of systematic random sampling, shall pick out an episode for analysis. The researcher shall divide the episodes (61 in total) into groups of four, thus giving us 15 episodes and shall analyze the fourth episode in each episode. At the end of the study, the results were as follows: - 47 % of episodes focused on establishing well developed characters - 40 % of episodes focused on establishing well developed female characters - 26 % of episodes focused on establishing the importance of the setting and the world As such, all the assumptions that the researcher made at the beginning of this study have all been confirmed. This thus demonstrates what made ATLA such an effective series were the character being presented as complex, multi-dimensional, and heavily nuanced characters that are motivated by a vast multitude of factors, the treatment of their female characters which were depicted not as ?strong female characters? but as strong characters who just happen to be female, and the heavily nuance world that gave the series a sense of grandness and scale.